Electronic cigarettes disrupt lung lipid homeostasis and innate immunity independent of nicotine - Madison, Matthew C.; Landers, Cameron T.; Gu, Bon-Hee; Chang, Cheng-Yen; Tung, Hui-Ying; You, Ran; Hong, Monica J.; Baghaei, Nima; Song, Li-Zhen; Porter, Paul; Putluri, Nagireddy; Salas, Ramiro; et al. (The Journal of Clinical Investigation, 2020)
Electronic nicotine delivery systems (ENDS) or e-cigarettes have emerged as a popular recreational tool among adolescents and adults. Although the use of ENDS is often promoted as a safer alternative to conventional cigarettes, few comprehensive studies have assessed the long-term effects of vaporized nicotine and its associated solvents, propylene glycol (PG) and vegetable glycerin (VG). Here, we show that compared with smoke exposure, mice receiving ENDS vapor for 4 months failed to develop pulmonary inflammation or emphysema. However, ENDS exposure, independent of nicotine, altered lung lipid homeostasis in alveolar macrophages and epithelial cells. Comprehensive lipidomic and structural analyses of the lungs revealed aberrant phospholipids in alveolar macrophages and increased surfactant-associated phospholipids in the airway. In addition to ENDS-induced lipid deposition, chronic ENDS vapor exposure downregulated innate immunity against viral pathogens in resident macrophages. Moreover, independent of nicotine, ENDS-exposed mice infected with influenza demonstrated enhanced lung inflammation and tissue damage. Together, our findings reveal that chronic e-cigarette vapor aberrantly alters the physiology of lung epithelial cells and resident immune cells and promotes poor response to infectious challenge. Notably, alterations in lipid homeostasis and immune impairment are independent of nicotine, thereby warranting more extensive investigations of the vehicle solvents used in e-cigarettes.